2019
DOI: 10.1111/1750-3841.14505
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Ameliorated Oxidative Stress and Inflammation in Type 2 Diabetic Rats

Abstract: We aim to study the antioxidative and anti-inflammatory effects of lycopene on type 2 diabetes mellitus (T2DM) rats, anticipating a complementary strategy for the prevention of long-term complications of T2DM. In this study, rats with streptozotocin-induced diabetes were divided into four groups, receiving a 10-week lycopene intervention: DM, DM + low dose of lycopene (L), DM + medium dose of lycopene (M), and DM + high dose of lycopene (H) group with 0, 5, 10, and 15 mg/kg BW lycopene, respectively. At the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…Oxidative stress in the aorta can cause endothelial dysfunction, an initiator and contributing factor to cardiovascular complications of diabetes. 16 Decreased MDA and increased SOD by lycopene treatment, as shown by Zhu et al, are also consistent with many other studies 18,24,25,30,[32][33][34][35][36][37][38][39][40] . A similar study conducted on patients with diabetes showed that lycopene supplementation (4 mg once daily for 3 months) can reduce oxidative stress, as seen from a decrease in MDA and xanthine oxidase levels and an increase in antioxidants such as SOD, GSH, GPx, and GR.…”
Section: Lycopene Ameliorates Oxidative Stress In Dmsupporting
confidence: 89%
See 2 more Smart Citations
“…Oxidative stress in the aorta can cause endothelial dysfunction, an initiator and contributing factor to cardiovascular complications of diabetes. 16 Decreased MDA and increased SOD by lycopene treatment, as shown by Zhu et al, are also consistent with many other studies 18,24,25,30,[32][33][34][35][36][37][38][39][40] . A similar study conducted on patients with diabetes showed that lycopene supplementation (4 mg once daily for 3 months) can reduce oxidative stress, as seen from a decrease in MDA and xanthine oxidase levels and an increase in antioxidants such as SOD, GSH, GPx, and GR.…”
Section: Lycopene Ameliorates Oxidative Stress In Dmsupporting
confidence: 89%
“…28 In DM, there is an increase of oxidative stress biomarkers ). 29,30 Due to the highly reactive nature of ROS and its short half-life, it is easier to estimate oxidative stress in DM by measuring its oxidation target products, such as lipid peroxidation products (MDA, ox-LDL, and thiobarbituric acid reactive substances [TBARS]), oxidized proteins (protein carbonyl), and nucleic acid oxidation product (8-OHdG). 31 In a study conducted by Zhu et al, administration of lycopene attenuates the increase in MDA and a decrease of SOD activity in the aorta of diabetic rats significantly and dose-dependently.…”
Section: Lycopene Ameliorates Oxidative Stress In Dmmentioning
confidence: 99%
See 1 more Smart Citation
“…Intake of carotenoids has been associated with risk reduction of lifestyle-related diseases [ 11 , 12 , 13 , 14 ] and high lycopene levels on plasma have been associated with a reduction of the cardiovascular disease risk [ 15 ]. Some reports described potential mechanisms of lycopene function for the prevention of lifestyle-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Carotenoids such as beta-carotene and lycopene play an important role in antioxidant defence, protecting the plasma membrane against lipid peroxidation (Tuncer et al, 2014). The antioxidant effect of lycopene has been demonstrated in diabetic rats, in which the compound protected against diabetic progression, and prevented further complications, because of its capacity to refine oxidative stress and inflammation, and improve the systemic antioxidative capacity (Zheng et al, 2019). In addition, recent studies have presented encouraging data about the use of lycopene in freezing extenders for bovine semen (Tuncer et al, 2014;Bucak et al, 2015) and turkey semen (Rosato et al, 2012a), including the preservation of motility, acrosome and DNA integrity, and a reduction in sperm lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%